Chemical Sample Processing for Combined Selenium Isotope and Selenium‐Tellurium Elemental Investigation of the Earth's Igneous Reservoirs. (27th February 2018) - Yierpan, Aierken; König, Stephan; Labidi, Jabrane; Kurzawa, Timon; Babechuk, Michael G.; Schoenberg, Ronny
Abstract: The redox‐sensitive, chalcophile, and volatile Se stable isotope system offers new perspectives to investigate the origin and evolution of terrestrial volatiles and the roles of magmatic and recycling processes in the development of the redox contrast between Earth's reservoirs. Selenium isotope systematics become more robust in a well‐constrained petrogenetic context as can be inferred from Se‐Te elemental signatures of sulfides and igneous rocks. In this study, we present a high‐yield chemical sample processing method that allows the determination of Se‐Te concentrations and Se isotope composition from the same sample digest of silicate rocks by hydride generation isotope dilution (ID) quadrupole inductively coupled plasma mass spectrometry (ICP‐MS) and double spike (DS) multicollector (MC)‐ICP‐MS, respectively. Our procedure yields ∼80% Se‐Te recoveries with quantitative separation of relevant interfering elements such as Ge and HG‐buffering metals. Replicate analyses of selected international reference materials yield uncertainties better than 0.11‰ (2 s.d.) on δ 82/76 Se and 3% (r.s.d.) on Se concentration for DS MC‐ICP‐MS determinations for as low as ∼10 ng sample Se. The precision of Se‐Te concentration measurements by ID ICP‐MS is better than 3% and 5% (r.s.d.) for total amounts of ∼0.5–1 ng Se and ∼0.2–0.5 ng Te, respectively. The basaltic reference materials have variable Se‐Te contents, but their δ 82/76 Se values are rather uniform (on average 0.23 ± 0.14‰; 2 s.d.) and different from the chondritic value. This altogether provides the methodology and potential to extend the limited data set of coupled Se isotope and Se‐Te elemental systematics of samples relevant to study the terrestrial igneous inventory. Key Points: High‐precision Se stable isotope and Se‐Te concentration analyses from the same sample digest New Se isotope data for five international silicate reference materials and Se isotopic difference between basalts and chondrites Potential to study the Earth's igneous reservoirs and mantle perspective on the volatile evolution